A survey of the influenza vaccination uptake among student nurses: prevalence and predictive factors - Hunt, Charlotte (2011)
Background: Influenza is an important cause of mortality and morbidity worldwide, resulting in up to five million deaths annually. Seasonal influenza affects up to 20% of the UK population annually. Vaccination of healthcare professionals has been reported to reduce the morbidity and mortality of patients, yet the uptake of the cost-free vaccination amongst healthcare workers is characteristically less than 25% across Europe. The main reason to reject the vaccination is reported to be a fear of side effects. However, those who accept the vaccination do so to protect themselves. Student nurses are eligible to have the cost-free influenza vaccination, though there is limited literature to suggest the uptake rate within this population.